FSQM 2020
DOI: 10.7176/fsqm/95-09
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Smallholder Farmers to Climate Related Shocks in Kinakomba Ward, Tana River County, Kenya

Abstract: According to IPCC, (2007) Vulnerability is the degree to which a system is susceptible to, and unable to cope with, adverse effects of climate change, including climate variability and extremes. It is a function of exposure, sensitivity, and adaptive capacity (Marshall et al. 2010; Wongbusarakum and Loper 2011, Mucke 2012). The study sought to determine the vulnerability to climate related shocks among smallholder farmers in Kinakomba Ward. The main purpose of the study was to assess the extent to which, expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…The high level of exposure by various respondents could mean that it contributed more to vulnerability than other factors particularly sensitivity and adaptive capacity. This is consistent with the findings of [32] who reported that exposure contributed more than adaptive capacity and sensitivity to the cumulative vulnerability among smallholder farmers in Tana River, a county where smallholder farmers are dependent on wetland and related resources for their livelihoods. Elsewhere, high levels of exposure could have been attributed to various climate risks and factors as reported by many authors.…”
Section: Exposure and Vulnerability To Climatic Hazardssupporting
confidence: 92%
“…The high level of exposure by various respondents could mean that it contributed more to vulnerability than other factors particularly sensitivity and adaptive capacity. This is consistent with the findings of [32] who reported that exposure contributed more than adaptive capacity and sensitivity to the cumulative vulnerability among smallholder farmers in Tana River, a county where smallholder farmers are dependent on wetland and related resources for their livelihoods. Elsewhere, high levels of exposure could have been attributed to various climate risks and factors as reported by many authors.…”
Section: Exposure and Vulnerability To Climatic Hazardssupporting
confidence: 92%